State-of-the-Art Review: Sex Hormone Therapy in Trauma-Hemorrhage. Issue 3 (5th March 2022) - Lang, Eric; Abdou, Hossam; Edwards, Joseph; Patel, Neerav; Morrison, Jonathan J.
Abstract : Abstract: Trauma-hemorrhage is the leading cause of prehospital and early in-hospital deaths, while also significantly contributing to the later development of multisystem organ dysfunction/failure and sepsis. Common and advanced resuscitative methods would potentially demonstrate benefits in the prehospital setting; however, they face a variety of barriers to application and implementation. Thus, a dialogue around a novel adjunct has arisen, sex hormone therapy. Proposed candidates include estradiol and its derivatives, metoclopramide hydrochloride/prolactin, dehydroepiandrosterone, and flutamide; with each having demonstrated a range of salutary effects in several animal model studies. Several retrospective analyses have observed a gender-based dimorphism in mortality following trauma-hemorrhage, thus suggesting that estrogens contribute to this pattern. Trauma-hemorrhage animal models have shown estrogens offer protective effects to the cardiovascular, pulmonary, hepatic, gastrointestinal, and immune systems. Additionally, a series of survival studies utilizing 17α-ethinylestradiol-3-sulfate, a potent, water-soluble synthetic estrogen, have demonstrated a significant survival benefit and beneficial effects on cardiovascular function. This review presents the findings of retrospective clinical studies, preclinical animal studies, and discusses how and why 17α-ethinylestradiol-3-sulfate should be considered for investigation within a prospective clinical trial.